2020
DOI: 10.1007/s11430-019-9618-7
|View full text |Cite
|
Sign up to set email alerts
|

Tidal variation of total suspended solids over the Yangtze Bank based on the geostationary ocean color imager

Abstract: Hourly mapping by a Geostationary Ocean Color Imager was used to reveal the spatial pattern and tidal variation of total suspended solids (TSS) over the Yangtze Bank in the Yellow and East China Seas during the winter. The TSS form a tongueshaped structure, which decreases further offshore in a stepwise manner. The stepwise change is separated by two fronts of TSS, which are located near the 20-m and 50-m isobaths. The tidal variation of TSS concentration during the study period is evident and can be divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…Framinan and Brown (1996) found that the frontal density distribution of turbidity fronts was highly consistent with the distribution of tidal mixing intensity in the Río La Plata Estuary, underlining a strong tidal control mechanism. In addition, tide‐induced vertical mixing was determined to be the dominant mechanism of frontogenesis along the Yellow Sea coast (Hu et al., 2016) and over the Yangtze Bank (Y. Zhou, Xuan, et al., 2020). Romero‐Rodriguez et al.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Framinan and Brown (1996) found that the frontal density distribution of turbidity fronts was highly consistent with the distribution of tidal mixing intensity in the Río La Plata Estuary, underlining a strong tidal control mechanism. In addition, tide‐induced vertical mixing was determined to be the dominant mechanism of frontogenesis along the Yellow Sea coast (Hu et al., 2016) and over the Yangtze Bank (Y. Zhou, Xuan, et al., 2020). Romero‐Rodriguez et al.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies have demonstrated that GOCI‐derived SSC images could be applied to highly turbid coastal waters (Choi et al., 2014; H. Yang, Choi, et al., 2014). GOCI Level‐2 SSC data were used to validate the model simulation results in the ECS (Y. Wang, Wu, Lin, et al., 2019) and extract SSFs in the Yellow Sea (Hu et al., 2016), Gyeonggi Bay (H. Yang et al., 2016), the ECS (Yin & Huang, 2016), and over the Yangtze Bank (Y. Zhou, Xuan, et al., 2020). Rather than estimating SSCs, we specifically focus on SSF dynamics based on the hourly SSC data obtained for the 10‐year period from April 1, 2011, to March 31, 2021.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations